An autopsy case of death due to metabolic acidosis after citric acid ingestion. Issue 6 (November 2015) - Ikeda, Tomoya; Usui, Akihito; Matsumura, Takashi; Aramaki, Tomomi; Hosoya, Tadashi; Igari, Yui; Ohuchi, Tsukasa; Hayashizaki, Yoshie; Usui, Kiyotaka; Funayama, Masato
Highlights: A case of death after drinking a commercial citric acid beverage is reported. Cause of death was severe metabolic acidosis and hypotension. Autopsy findings were esophageal mucosal and submucosal degeneration. Autopsy also showed vessel thrombosis and cellular infiltration of the esophagus. Abstract: A man in his 40s was found unconscious on a sofa in a communal residence for people with various disabilities. He appeared to have drunk 800 ml of undiluted citric acid from a commercial plastic bottle. The instructions on the label of the beverage specified that the beverage be diluted 20- to 30-fold before consumption. The patient was admitted to an emergency hospital with severe metabolic acidosis (pH, 6.70; HCO3 −, 3.6 mEq/L) and a low ionized calcium level (0.73 mmol/L). Although ionized calcium and catecholamines were continuously administered intravenously to correct the acidosis, the state of acidemia and low blood pressure did not improve, and he died 20 h later. Citric acid concentrations in the patient's serum drawn shortly after treatment in the hospital and from the heart at autopsy were 80.6 mg/ml and 39.8 mg/dl, respectively (normal range: 1.3–2.6 mg/dl). Autopsy revealed black discoloration of the mucosal surface of the esophagus. Microscopically, degenerated epithelium and neutrophilic infiltration in the muscle layer were observed. In daily life, drinking a large amount of concentrated citric acid beverage is rare as a cause of lethal poisoning. However, persons with mental disorders such as dementia may mistakenly drink detergent or concentrated fluids, as in our case. Family members or facility staff in the home or nursing facility must bear in mind that they should not leave such bottles in places where they are easily accessible to mentally handicapped persons.